2021
DOI: 10.3389/fphys.2021.791834
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Function of ABC Proteins in Fish Intestine

Abstract: In fish, the intestine is fundamental for digestion, nutrient absorption, and other functions like osmoregulation, acid-base balance, and excretion of some metabolic products. These functions require a large exchange surface area, which, in turn, favors the absorption of natural and anthropogenic foreign substances (xenobiotics) either dissolved in water or contained in the food. According to their chemical nature, nutrients, ions, and water may cross the intestine epithelium cells’ apical and basolateral memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 217 publications
(347 reference statements)
0
13
0
1
Order By: Relevance
“…Therefore, we demonstrate here for the first time a direct link between dietary LPLs and improved liver lipid metabolism. For instance, some of the proteins upregulated by dietary LPLs are relevant metabolic enzymes: long-chain fatty acid—CoA ligase 1 (ACSL1), which activates long-chain fatty acids for both the degradation via beta-oxidation and synthesis of cellular lipids [ 45 ]; cytochrome P450 1A1 (CYP1A1), which is involved in the oxidation of a variety of structurally unrelated compounds, including steroids, fatty acids, and xenobiotics [ 46 ]; fatty acid amide hydrolase 2 (FAAH2), which degrades bioactive fatty acid amides [ 47 ]; acyl-CoA desaturase (SCD), which plays an important role in regulating the expression of genes that are involved in regulating mitochondrial fatty acid oxidation [ 48 ]; ATP-binding cassette sub-family D member 3 (ABCD3), which is a probable transporter involved in the transport of branched-chain fatty acids and C27 bile acids into the peroxisome [ 49 ], the latter function being a crucial step in bile acid biosynthesis; and fatty-acid-binding protein (FABP2), which plays a role in the intracellular transport of long-chain fatty acids and their acyl-CoA esters [ 50 ]. FABP2 is probably involved in triglyceride-rich lipoprotein synthesis, favoring lipid release from the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we demonstrate here for the first time a direct link between dietary LPLs and improved liver lipid metabolism. For instance, some of the proteins upregulated by dietary LPLs are relevant metabolic enzymes: long-chain fatty acid—CoA ligase 1 (ACSL1), which activates long-chain fatty acids for both the degradation via beta-oxidation and synthesis of cellular lipids [ 45 ]; cytochrome P450 1A1 (CYP1A1), which is involved in the oxidation of a variety of structurally unrelated compounds, including steroids, fatty acids, and xenobiotics [ 46 ]; fatty acid amide hydrolase 2 (FAAH2), which degrades bioactive fatty acid amides [ 47 ]; acyl-CoA desaturase (SCD), which plays an important role in regulating the expression of genes that are involved in regulating mitochondrial fatty acid oxidation [ 48 ]; ATP-binding cassette sub-family D member 3 (ABCD3), which is a probable transporter involved in the transport of branched-chain fatty acids and C27 bile acids into the peroxisome [ 49 ], the latter function being a crucial step in bile acid biosynthesis; and fatty-acid-binding protein (FABP2), which plays a role in the intracellular transport of long-chain fatty acids and their acyl-CoA esters [ 50 ]. FABP2 is probably involved in triglyceride-rich lipoprotein synthesis, favoring lipid release from the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the apical distribution on enterocytes, little is known regarding how ABC transporters interact with the GM. Recent studies reported that their expression is influenced by gut microbes (pathogenic or otherwise) ( Figure 2 ) [ 74 ].…”
Section: The Structure and Functions Of The Intestinal Barriermentioning
confidence: 99%
“…Marine teleost fish have a number of physiological features that may render them more susceptible to the uptake of APIs from the GIT than FW fish (Figure b). First of all, being hypo-osmotic to their environment, they consume large volumes of seawater for osmoregulatory purposes. , Second, cortisol stimulates cellular apoptosis in the GIT of fish acclimating to saltwater (SW), thereby making the epithelium more permeable than in FW fish . Substantial amounts of bicarbonate ions are also secreted into the intestines of marine fish, precipitating divalent cations such as calcium and thereby further promoting the absorption of water .…”
Section: Susceptibility Of Fish To Human Apis In the Environment – In...mentioning
confidence: 99%